PERBEDAAN HASIL BELAJAR SISWA PADA MATERI KEKAYAAN BUDAYA INDONESIA MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING - Annisa Delia Futri; Yuli Mulyawati; Annisa Nurramadhani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the differences in student learning outcomes on the topic of Indonesia's cultural heritage through the implementation of the problem- based learning (PBL) model in Grade IV at SDN Gadog 01, Tamansari Subdistrict, Bogor Regency. This research uses a quantitative method with a quasi- experimental design involving two groups selected through simple random sampling. The analysis techniques used include prerequisite tests such as the normality test, variance homogeneity test, and hypothesis testing using the t-test. The results showed that the average N-Gain score in the experimental class using the Problem-Based Learning model fell into the high category, while the control class using the Discovery Learning model had a moderate average N-Gain score. Based on the research findings, it can be concluded that there are significant differences instudent learning outcomes on the topic of Indonesia'scultural heritage through the implementation of the problem-based learning model in Grade IV at SDN Gadog 01, Tamansari Subdistrict, Bogor Regency.